1981
DOI: 10.1111/j.1365-2265.1981.tb00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Prolactin and Milk Production in Women During a Lactation Period of Thirty Months

Abstract: Serum prolactin was measured in single blood samples collected from 219 nursing mothers of the Kivu region (Zaïre) during 30 post-partum months. In addition the number of feeding episodes per day and the amount of milk given to the child in 24 h were recorded. The mean serum prolactin levels remained around 1000 mu/l during the first 15 months of lactation and fell during the next 3 months to 550 mu/l. A decline in milk production per day occurred during the second year, but it was less marked than that of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 5 publications
2
22
0
1
Order By: Relevance
“…Despite this decline, basal prolactin at 6 months postpartum was still higher than the concentration reported for non-lactating women at 6 months postpartum (Gross & Eastman, 1983). Similar decreases in basal prolactin during lactation have been found for women in the USA during the first month of lactation and from 1 to 7 months of lactation (Noel et al 1974;Tyson et al 1975;Battin, Marrs, Fleiss & Mishell, 1985), in Zaire from approximately I to 30 months of lactation (Hennart et al 1981) and in the Philippines from 1 to 20 months of lactation (Gross, Haynes, Eastman, Balderrama-Guzman & del Castillo, 1980). Basal prolactin, at 1 month of lactation, ranged from as low as 15 + 1.4 ug/l (n = 3) (Noel et al 1974) to 119 + 19.1 ,ug/l (n = 24) measured in the present study (Fig.…”
Section: Plasma Prolactin and Milk Synthesissupporting
confidence: 58%
See 1 more Smart Citation
“…Despite this decline, basal prolactin at 6 months postpartum was still higher than the concentration reported for non-lactating women at 6 months postpartum (Gross & Eastman, 1983). Similar decreases in basal prolactin during lactation have been found for women in the USA during the first month of lactation and from 1 to 7 months of lactation (Noel et al 1974;Tyson et al 1975;Battin, Marrs, Fleiss & Mishell, 1985), in Zaire from approximately I to 30 months of lactation (Hennart et al 1981) and in the Philippines from 1 to 20 months of lactation (Gross, Haynes, Eastman, Balderrama-Guzman & del Castillo, 1980). Basal prolactin, at 1 month of lactation, ranged from as low as 15 + 1.4 ug/l (n = 3) (Noel et al 1974) to 119 + 19.1 ,ug/l (n = 24) measured in the present study (Fig.…”
Section: Plasma Prolactin and Milk Synthesissupporting
confidence: 58%
“…In addition, increased suckling frequency is also associated with increased milk production (Hennart, Delogne-Desnoeck, Vis & Robyn, 1981;Rattigan, Ghisalberti & Hartmann, 1981;De Carvalho, Robertson, Friedman & Klaus, 1983) and is recommended to women as a practical means of increasing an inadequate supply of milk (Phillips, 1991). In this connection, drugs which increase prolactin secretion also have been recommended for women with infants who are failing to thrive (Lawrence, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Whether the decline in breast volume is due to mobilization of fat from the breast, apoptosis caused by endocrine and local factors, or a combination of these effects, we have found that even when the breast volume had returned to a minimum at 15 months, the combined 24 h milk production from both breasts of the mothers was still between 95 and 315 g. Hennart et al (1981) also found 24 h milk production of between 150 and 300 g from 15-18 months until 27-30 months. This suggests that while proliferation of breast tissue is necessary for sufficient milk production to sustain an infant, the breast does not need to be enlarged above pre-conception size to continue significant milk production.…”
Section: Subject Body Weight and Infant Growthmentioning
confidence: 84%
“…In rats, a deficiency of prolactin and growth hormone causes apoptosis in the mammary gland, which is reversible by prolactin treatment (Travers et al 1996). In women, Hennart et al (1981) found that prolactin concentrations in blood samples collected before breast feeds decreased gradually from 1-3 months to 12-15 months, then dropped sharply at 15-18 months to concentrations not different from non-pregnant non-lactating women. Our data showed that the breast volume returned to pre-conception size on average at 15 months, consistent with apoptosis occurring as a result of decreased blood prolactin concentrations.…”
Section: Subject Body Weight and Infant Growthmentioning
confidence: 94%
“…12 Prolactin increases mammary IgA-secreting plasma cells in mice, 13 and the pattern of milk oligosaccharide concentrations (high during early lactation and decreasing over the course of lactation) 14 parallels decreases in prolactin levels that occur over time. [15][16][17] These effects suggest that prolactin may contribute to the progressive changes in milk composition.…”
mentioning
confidence: 99%